2008
DOI: 10.1152/ajpcell.00154.2008
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Mg2+ is a voltage-dependent pore blocker of HCN channels

Abstract: Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are activated by membrane hyperpolarization that creates time-dependent, inward rectifying currents, gated by the movement of the intrinsic voltage sensor S4. However, inward rectification of the HCN currents is not only observed in the time-dependent HCN currents, but also in the instantaneous HCN tail currents. Inward rectification can also be seen in mutant HCN channels that have mainly time-independent currents (5). In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
5
14
0
Order By: Relevance
“…Once the microelectrodes were inside the cell, that is isolated from the extracellular buffer solution, an electrochemical potential difference signal was detected identifying the activity of Mg 2+ . The measured intracellular Mg 2+ concentration for human adipocytes was 0.4 to 0.5 mM and for frog oocyte it was 0.8 to 0.9 mM, closely consistent with the intracellular concentration reported in the literature (Nadler and Scott, 1994;Gabriel and Gunzel, 2007;Vemana et al, 2008;Lyashchenko and Tibbs, 2008).…”
Section: Measurements Of Intracellular Free Mg 2+ Concentrationssupporting
confidence: 90%
“…Once the microelectrodes were inside the cell, that is isolated from the extracellular buffer solution, an electrochemical potential difference signal was detected identifying the activity of Mg 2+ . The measured intracellular Mg 2+ concentration for human adipocytes was 0.4 to 0.5 mM and for frog oocyte it was 0.8 to 0.9 mM, closely consistent with the intracellular concentration reported in the literature (Nadler and Scott, 1994;Gabriel and Gunzel, 2007;Vemana et al, 2008;Lyashchenko and Tibbs, 2008).…”
Section: Measurements Of Intracellular Free Mg 2+ Concentrationssupporting
confidence: 90%
“…It has previously been shown that intracellular Mg 2+ acts as a voltage dependent blocker of open HCN channels [64], [65]. The voltage dependence of the block and its sensitivity to mutation of residues forming the inner face of the selectivity filter is consistent with the Mg 2+ binding site lying close to or within the selectivity filter itself.…”
Section: Introductionsupporting
confidence: 54%
“…It should be noted that I h does not necessarily require hyperpolarization to open, as HCN channels have a tonically active leak current component (6771) that is blocked by ZD7288 (67, 72). Furthermore, HCN channels and D1Rs are found near a constellation of cAMP signaling proteins at dendritic spines, whereas HCN channels on dendrites have few cAMP signaling proteins nearby (26).…”
Section: Discussionmentioning
confidence: 99%